ЕДНА ГОДИНА ОД ПРИМЕНАТА НА ЗАКОНОТ ЗА ОДРЕДУВАЊЕ НА ВИДОТ И ОДМЕРУВАЊЕ НА ВИСИНАТА НА КАЗНАТА – ПРОБЛЕМИ И ПРЕДИЗВИЦИ - Tupanceski, Nikola; Deanoska Trendafilova, Aleksandra (MACEDONIAN ASSOCIATION FOR CRIMINAL LAW AND CRIMINOLOGY, 2017)
The authors of this paper address the issue of the legal determination of sentences, but primarily of the judicial sentencing as a particularly actual issue in the Republic of Macedonia lately. They elaborate the process of reformation of this institute, especially critically addressing the solutions of the provisions of the Law on determination of the type and meting out of the sentence. Despite the vague and even absurd solutions in some of the provisions of the Law, the authors present the perceptions and the facts about the work of judges, prosecutors and lawyers in the period of initial application of this law. Through specific indicators they specify that this Law violates the basic principles of criminal law, primarily the principle of individualization, that the law leads to unfair and aggravated punishment, and that it does not fulfil the purpose of its adoption which is uniform sentencing policy.
ONE YEAR OF THE IMPLEMENTATION OF THE LAW ON THE DETERMINATION OF THE TYPE OF SENTENCE AND THE DETERMINATION OF THE LENGTH OF THE SENTENCE - ISSUES AND CHALLENGES
Keywords: criminal policy, law, meting out, punishment, unification